Four-week administration of an energy and protein dense oral nutritional supplement improves micronutrient concentrations but does not completely correct deficiencies in institutionalized malnourished older adults - Sanchez, Manuel; Courtois-Amiot, Pauline; Capdepon, Audrey; Neveux, Nathalie; Gautry, Julien; Dorigny, Béatrice; Brossault, Ludovic; Bouillanne, Olivier; Aussel, Christian; Raynaud-Simon, Agathe; Cynober, Luc (Frontiers in Nutrition, 2023)
Introduction: Poor food intake is common among elderly living in nursing homes, leading to micronutrient deficiency (MD). There are no recommendations for the management of MD in malnourished older adults. Methods: We conducted a single arm, open-label, multicenter interventional study in institutionalized malnourished older adults to describe the effect of a 4-week daily energy and protein dense oral nutritional supplementation (ONS, 600 kcal, 30g protein per unit) containing 50% of the recommended daily micronutrient intake on micronutrient status. Plasma concentrations of vitamins (A, B9, B12, C, E), magnesium (Mg), selenium (Se) and zinc (Zn), and erythrocyte vitamin B9 were measured at baseline and after 4 weeks. Results: Forty-six participants completed the study (age 87.4±6.6). At baseline, the most frequent MD were Se (48%), Zn (35%), Mg (24%) and vitamin C (24%). Plasma concentrations of vitamins B9, B12, C and E, Mg, Se and Zn significantly increased and the proportion of subjects with at least one MD decreased (p = 0.006). However, after 4 weeks, 40% of subjects still had at least one MD. Discussion: ONS consumption improved micronutrient status but did not correct MD in all participants. Our data suggest that the prescription of vitamin, mineral and trace element supplementation should be considered in institutionalized malnourished older adults in addition to high energy and high protein ONS.